Dental hygiene : theory and practice - Darby, Michele Leonardi, 1949-; Walsh, Margaret M. (Saunders/Elsevier, 2010)
From the Publisher: Comprehensive and up to date, this practical textbook offers complete coverage of today's dental hygiene skills and theories-all based on the Human Needs Model for better hygienist/patient communication. With a strong focus on clinical application, each section closely follows the critical thinking and clinical assessment approach that a hygienist must use in the classroom, clinic, and practice. Clinical competencies at the beginning of each chapter provide a clear, quick overview of exactly what you need to know, and procedure boxes with detailed steps and rationales ensure that you understand the reasoning behind each step in the competencies. In addition, new chapters on caries risk assessment and the oral-systemic health connection keep you up to date with today's major areas of research. Each section takes you from conceptual foundations of dental hygiene through patient assessment, treatment, and evaluation. Scenario boxes challenge you to integrate complex information as you assess, diagnose, plan care, and evaluate the outcome of care. Client Education Issues and Legal, Ethical and Safety Issues boxes inform you of the latest information in these important areas. Critical Thinking exercises provide opportunities for independent thought and problem solving. Tables and boxes build upon and simplify information from the text, making study and review quick and easy. Evolve website contains free online resources, including weblinks, self-assessment quizzes, and professional development worksheets for student review. A reorganized section for Individuals with Special Needs includes chapters on Cleft Palate, Physical Abuse, Blood Diseases, and Mental Illness, all reflecting evidence-based research now available in these areas. New chapters on caries risk assessment and the oral-systemic health connection-hot topics in today's dental sciences. New anesthesia guidelines keep you up to date with what's new in pain and anxiety control. Essential resources and websites are now included at the end of each chapter for easy reference. New illustrations provide a fresh, reader-friendly design. Self-assessment quizzes are available online, all case-based to follow the NBDH format. Free online access to the Legal and Ethical Decision Making chapter, including an 'asset center' to assist you with clinical skills
Keywords: Dental hygiene; Dental hygienists; Oral Health